Correlates of international students' listening comprehension of Filipino speakers of English - Buzar, Jaime M.
Research findings on the academic problems of foreign students in foreign lands point out to English language inadequacy as the most serious problem that affects academic performance. The findings of the study pointed out to the relative differences in the subjects' comprehension of the lecture under two types of Filipino speakers of English. Subjects who listened to the lecture delivered by the good speaker obtained higher comprehension scores than those who listened to a poor speaker. There were significant relationships between listening comprehension and subjects' English language proficiency, self-concept of English proficiency, language background and cloze ability. The study concluded that the key factor in the listening comprehension of foreign students to oral communication of Filipinos is the speaker.